Pengaruh Penyalahgunaan Narkoba Terhadap Kesehatan Manusia (Studi Kasus Di Kalimantan Timur) - Prof. Dr. Fl. Sudiran, M.Si (Prodi Ilmu Administrasi Negara, 2016)
The objective of this research is to know the negative effectof the misue of drugs to the health.The backgrund of thisresearch is that there is a serious negative effect of the drugsincluding for the young generation such as the students fromprimary and secondary schools and the high education aswell. President Joko Widodo had ever said that every year 50(fifty) thousand persons of Indonesia dead becuase of it. Themethod of the it is discriptive-qualitative. The data collectionof the data by library research by taking from the magazinedaily news–paper, reports as well as the electronic media,spreading the questionair, observation and interview. Theresults of the researh are (1).The drugs has been misused bymany people here in East Kalimantan (2). Its spread is solarge that some persons and even the apparatus of the statehave involved in this illegal things, (3). The regulation of thedrugs articles are so weak that there are still many people arenot afraid of to involve the illegal distribution of it. Thesuggestions of the researche are (1). The regulation of thedrugs articles have to be harder punishment than nowdays,(2). The supervision of it has to continue and tight, (3). Thefamily situation has to be happy.